STRATEGI MENANGKAL RADIKALISME AGAMA DI KABUPATEN SUMBAWA BARAT - Wahyudi, Johan (JPP (Jurnal Politik Profetik), 2020)
The high spread of radical ideology in Indonesia has led to the potential and threat of spreading radical ideology to various regions. West Sumbawa Regency is one of the potential areas of the spread of radicalism, especially religious radicalism, because there were some social communities that have religious doctrine of the caliphate that contradicts with Pancasila. So it required some preventive efforts to overcome it. This research aims to find out the factors that trigger the rise of religious radicalism in West Sumbawa Regency and find out the efforts and strategies to prevent the entry of radical ideas in West Sumbawa Regency. This research was carried out in West Sumbawa Regency. Data collection was done by survey techniques through interviews using research questionnaires. Interviews were conducted with 30 respondents. The strategy of preventing religious radicalism was formulated using the SWOT analysis method. This study found that at least, there are 3 factors that can trigger religious radicalism in West Sumbawa Regency include; dissatisfaction with government policies, weak government oversight of schools indicated by radical movements, and religious understanding that felt the most right compared to other groups. Based on the findings and analysis results obtained in this study, it can be concluded that the strategy to ward off religious radicalism in West Sumbawa Regency is an S-O (Strengths-Opportunity) strategy, which is a strategy that utilizes existing strengths to seize opportunities.